PENYUSUNAN JOB DESCRIPTION MELALUI PROSES ANALISIS JABATAN UNTUK MENGATASI ROLE AMBIGUITY DI PT X - Devin Devin; Ivana Nethanya Lazuardi; Theofilus Ronald Laorence; Daniel Lie (PROSIDING SERINA, 2021)
The success of an organisation is closely linked with the employees’ performance. However, there are many obstacles which hinder them, thus affecting their organisational effectiveness. One organisation that faces problems is PT X, where employees often work overtime to complete their tasks. Some even continue working once they reach home after work, resulting in them feeling stressed out. This problem is due to the existence of role ambiguity in which there is inclarity about the completion of the tasks by each employee. Role ambiguity can be curbed by creating a job description (a list that explains what each employee actually does, how the employee does it, and what the working conditions of the job look like) for each position by carrying out a job analysis. Practitioners conducted job analysis using interview and questionnaire methods for two months and created 16 job descriptions in total. Evaluation is performed by obtaining feedback from the management and employees who are currently holding those designated positions. All employees are satisfied because with the job description they understand their job responsibilities clearly, do not complete the tasks that are not their responsibility, and only focus on completing tasks according to their respective positions. Additionally, the management strongly believes that this job description reduces the stress level of their employees who are experiencing the role ambiguity. Furthermore, the management is also advised to always monitor closely the implementation and update of the job description (if necessary) to prevent the recurrence of role ambiguity in PT X.